“I don’t feel like I have a big role here in Belgium” The societal participation of migrantised women in Antwerp (Belgium) - Kaya Klaver; Amal Miri; Lore Van Praag (Societal Impacts)
This study looks at the societal participation of migrantised women in Antwerp, Belgium, through an intersectional lens, focusing on their roles within civil society organizations (CSOs). Dominant integration discourses, shaped by cultural notions of agency and work, often overlook the contributions of these women, such as ‘hidden voluntary social work’ or unpaid work. Using ethnographic fieldwork and semi-structured interviews, this research – part of a larger (Blinded for review) – to shed light on the diverse ways these women participate in society. Despite their active participation, many feel their contributions are inferior, due to societal barriers, discrimination, and internalized feelings of inadequacy. This study fosters a broader recognition of diverse participation modes in integration policies, using an intersectional lens, and challenges dominant narratives that marginalize these efforts.